2014
DOI: 10.1186/2045-9912-4-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Activation of heme oxygenase-2 by menadione and its analogs

Abstract: BackgroundPreviously, we reported that menadione activated rat, native heme oxygenase-2 (HO-2) and human recombinant heme oxygenase-2 selectively; it did not activate spleen, microsomal heme oxygenase-1. The purpose of this study was to explore some structure–activity relationships of this activation and the idea that redox properties may be an important aspect of menadione efficacy.MethodsHeme oxygenase activity was determined in vitro using rat spleen and brain microsomes as the sources of heme oxygenase-1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
4
14
0
1
Order By: Relevance
“…In these experiments, the baseline activity represents HO activity. Within the naphthoquinone family, we found that many members acted similarly to MD by increasing CO formation while some others did not; our results of testing ~50 other naphthoquinones were reported earlier 6. The presence of a variety of chemical entities increased CO production many-fold; for example, OT-7116980337 (Otava, Toronto, Canada), SI-1606 (Sniekus Innovations, Kingston, Canada) and VV-101 (St. Sava Bioanalytical & Medical Research, Kingston, Canada) ( Table 1 ).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In these experiments, the baseline activity represents HO activity. Within the naphthoquinone family, we found that many members acted similarly to MD by increasing CO formation while some others did not; our results of testing ~50 other naphthoquinones were reported earlier 6. The presence of a variety of chemical entities increased CO production many-fold; for example, OT-7116980337 (Otava, Toronto, Canada), SI-1606 (Sniekus Innovations, Kingston, Canada) and VV-101 (St. Sava Bioanalytical & Medical Research, Kingston, Canada) ( Table 1 ).…”
Section: Resultssupporting
confidence: 82%
“…This was the case of MD analogs such as the 2,4-dimethoxy-2-methylnaphthoquinone and 2,5,6,7,8-pentafluoro-3-methyl-1,4-naphthalenedione; in the former, quinone oxygens that are essential for redox function have been replaced by methoxy groups, and the fluorines of pentafluora analog would interfere with electron flow by virtue of their high electron affinity. Neither of these compounds resulted in an increase in CO production 6. Similarly our observation that SI-441 did not increase CO production may be attributed to preventing redox cycling; this could be due the inductive effect of the electronegative Br atom and electron delocalization of the tautomeric forms via intramolecular hydrogen bonding involving the H of the –OH and the carbonyl group as discussed in the review by Brunmark and Cadenas 20.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The HO-2 isoform is considered to be constitutively expressed, but expression can change in response to certain stimuli (hypoxia, glucocorticoids) (Han et al 2005;He et al 2010;Vukomanovic et al 2011;Zhang et al 2006). In contrast to HO-1 expression in the brain, HO-2 is the predominant isoform expressed in neurons.…”
Section: Ho-1 Expression In Multiple Brain Regions Associates With Csmentioning
confidence: 99%
“…Вікасол здебільшого використовується як токсикант у моделюванні оксидаційного стресу [11,33]. За останні роки дослідження фармакологічних властивостей хінонів значно активізувались [3,8,11,13,24,31], хоча їх вплив на жирнокислотний склад тканин вивчено не достатньо. Описано вплив вікасолу на процеси транскрипції та активації чинників, які задіяні у ланцюгу антиоксидантної відповіді клітини.…”
Section: біохіміяunclassified